The Time is Gone!? Pink Floyds "Time" (1973) - Hantschel, Florian; Justus Liebig University Giessen (My University, 2012)
This paper provides a hermeneutic approach on Pink Floyds popular song "Time" from 1973s album Dark Side Of The Moon. The primary aim of this examination is the analysis of the conceptual connection of music and lyrics in this song. Moreover, derivation of semantic meaning potential is used to form an intersubjectively verifiable song interpretation. All in all, the main results of this analysis suggest a close connection of the songs musical parameters, i.e. form, harmony, melody, rhythm as well as sound, and its lyrical theme: (1) first the musique concrète in the songs introduction and the subsequent instrumental passage establish evident semantic relations to the following lyrical theme of fleeting time, (2) a devils circle of transitoriness of life is presented in the songs lyrics and is musically mirrored by periodic formal and harmonic repetitions, (3) the ambivalence of the bridges negative lyrics in combination with the sweet melodic thirds in the vocals suggests a melancholic atmosphere, (4) the lyrics description of a human life from birth to death is reflected in the formal structure and the harmony of »Time« as well as in the conceptual arrangement of Dark Side Of The Moons first LP-side from »Speak To Me« to »The Great Gig In The Sky«.
Keywords: ddc:780